Meningocele and Meningoencephalocele in Piglets: Pathologic and Imaging Aspects - de Sousa, Marilaine Carlos; de Oliveira, Lilian Porto; Muramoto, Caterina; de Mendonça, Múcio Fernando Ferraro; da Silva, Antonio Wesley Oliveira; Leal, Paula Veloso; Peixoto, Tiago da Cunha (Acta Scientiae Veterinariae, 2020)
Background: Meningocele and meningoencephalocele are rare congenital deformities characterized by herniation of the meninges and of the meninges and brain tissue through a bone defect in the skull (cranioschisis), respectively. Descriptions of these malformations in pigs are scarce in the international literature and non-existent in Brazil, with only one case of cranioschisis with brain exposure (without protrusion of the meninges and covered by skin) reported to date. Here, we report a case of meningocele and another of meningoencephalocele in piglets in the state of Bahia and describe the main related anatomopathological and imaging characteristics (radiographic and ultrasonographic). Case: The congenital malformations occurred in newborn piglets from a farm located in the city of Catu, Bahia, Brazil, which presented with an evident large saccular area positioned dorsally to the head. The animals died 48 h after birth and were referred to the Laboratory of Animal Pathology of the Federal University of Bahia, for the studies and diagnostic conclusion. Postmortem ultrasound examinations showed that the region was filled with fluid and associated with a small brain protrusion in case 1 and a defect in the skull bone, which had its orifice dimensions estimated. Despite the superimposition of structures, the skull malformation was identified on radiographic examination (case 1) and measured on ultrasonographic examination (cases 1 and 2). During necropsy, the piglets presented with a marked marked bulge of saccular appearance under the skin in the frontal region. The saccular formation was floating, internally covered by dura mater and filled with reddish serous liquid (liquor). Discussion: The diagnoses of meningoencephalocele and meningocele in newborn piglets were established based on morphological changes identified on ultrasound and necropsy. Although the ultrasound diagnosis of meningocele and meningoencephalocele are routinely made in human medicine, they are still limited in veterinary medicine in cases of malformations in production animals, with no case report in pigs. A Brazilian textbook on pig diseases cites these diseases among the main malformations that affect this species, although data on epidemiology and anatomopathological and imaging findings are not described, which highlights the importance of this study. As for the etiology of these malformations, the occurrence of two cases in piglets from the same farm in the present report may suggest the presence of genetic factors. The confirmation that inbreeding is common at farms where the cases occurred, and absence of herd renewal since 2014 (continuous use of the same breeders), reinforced this hypothesis, since inbreeding results in serious reproductive and productive disorders due to increased homozygosis and, consequently, due to the frequency of genotypes with recessive genes that cause various malformations in animals. This fact reinforces the need to make producers aware of the importance of avoiding inbreeding and the use of breeders that have generated malformed piglets to reduce the frequency of malformations. Additional studies on congenital malformations in pigs in Brazil are necessary because of the scarcity of existing data, particularly regarding the etiology and anatomopathological and imaging characteristics of these diseases.